Customized double‐shell immobilization device combined with VMAT radiation treatment of basosquamous cell carcinoma of the scalp. Issue 2 (24th January 2019) - Mail, Noor; Al‐Ghamdi, Suliman M.; Chantel, Carelse; Sedhu, Farid; Rana, Atique; Saoudi, Abdelhamid
Abstract: Malignancies with a superficial involvement of the scalp/skull present technical challenges for radiation‐treatment‐planning, such as achieving skin coverage with the prescribed dose and with the desirable conformity, homogeneity, and lower brain dose. We report a radiotherapy treatment technique for a patient diagnosed with diffuse basosquamous cell carcinoma of the scalp and adjacent skull‐bone. This study presents the plan's quality parameters, patient's dosimetry, and patient's outcome. The patient was treated using volume‐modulated‐arc therapy (VMAT) and a double‐shell‐bolus full‐head device (DSBFD) designed for patient immobilization and better skin coverage. A VMAT plan was generated using an Eclipse treatment‐planning system for a prescribed dose of 60 Gy in 30 fractions. The treatment plan was analyzed to determine the conformity index (CI), the homogeneity index (HI), the target‐coverage, and the dose to the organs‐at‐risk (OARs). Skin‐doses were measured using optically stimulated luminescence (OSL) dosimeters. Clinical follow‐up was performed by the radiation oncologist during and after the course of radiotherapy. With regard to planning target volume (PTV) coverage, the V 95 was 99%. The measured and calculated dose to the skin was in the range 100–108% of the prescribed dose. The mean brain‐PTV dose was 711 cGy. The CI and HI were 1.09 and 1.08, respectively. The mean positioning accuracy for the patient over the course of treatment was within 2 mm. The measured accumulated skin dose and planning dose was agreed within 2%. Clinical examination of the patient 6 months after radiotherapy showed good response to the treatment and a 90% reduction in scarring. The DSBFD technique combined with RapidArc treatment was useful in terms of the target dose distribution and coverage. Daily patient alignment was found very precise, reproducible and less time‐consuming.